Women in Buddhism Through Gender Perspective - Ghimire, Chandra Kala (Journal of Buddhist Studies (T.U.), 2024)
A society’s view towards women can be studied using a gender perspective in religion. Despite non-discrimination in teachings, gender discrimination in practices has influenced females in the Buddhist monastic sangha and laity. This exploratory article aims to demonstrate whether Buddhism is a gender-biased or gender-friendly religion. To find the answer, the article investigates the status of women during Buddha’s time, the cause of women’s renunciation, the establishment of the Bhikshuni Sangha and the supernatural power of Bhikshunis, women’s contributions to the making of Buddha, and the status of women in the Mahayana/Vajrayana tradition. Gender discrimination can be studied in terms of language, profession, social status, daily life, beliefs, norms, cultural practices, dress, and ornaments, among others. Because society was male-dominated at the time of Buddha, some laypeople and monastic members used gender-biased language and practices. Not only in this life, but during Siddhartha’s bodhisattvacarya, women in various relationships helped him become a Buddha. As a result, women could not be denied the opportunity to make a Buddha. During the further development of Buddhism into various yanas, Mahayana and Vajrayana provide equal footing for women in theory, but discrimination still exists in practice. Mahayana and Vajrayana Buddhism gives women a higher status than Sravakayana, respecting them as female Buddhas and the wisdom aspect of the enlightened mind. With the advancement of Buddhism, gender issues of baseness based on gender are diminishing. Gender is the subject of worldly beings that stems from a defiled mind. In the realm of enlightenment, there is no male or female. It goes beyond the idea of sex and gender.